Requirements for redesigning the interface of Iraqi e-government portal - AbdulWahid, Hayder Sabah (2015)
Many countries have provided their government services to the people online. However, Iraq is still looking for opportunities to implement the online technology for their government services. The initiatives to venture into online government services, or called electronic government (e-government) have not shown good return. Although the e-government is available, people still prefer to work on traditional way, or enter into the e-government modules through improper channels. Hence, they are viewed as not using the e-government portal. Many factors were identified influencing the disadvantages of the existing e-government portal; nevertheless the design of the front office is not making users attracted to enter into the portal through the proper home page. In contrast, the users tend to go directly to the module they intend to. Hence, his study deduces that the user interface of the front office of the portal was not usable, not supporting user experience. This study proposes a set of elements for the Iraqi e-government portal to ensure that it is perceived usable in terms of usefulness and ease-of-use. This study develops the prototype that incorporates the elements as Iraqi e-government portal (Ie-gP). Therefore, the aim of the study is to propose a set of elements that make the Ie-gP usable from users‟ perception. To accomplish that, three specific objectives are formulated: (1) to determine the interface elements for the front office of Ie-gP, (2) to design and develop the front office of Ie-gP, and (3) to evaluate the ease-of-use of the front office of Ie-gP. Comparative analysis, prototyping, and experimental studies are used to accomplish the objectives and aim. General findings show that Ie-gP is perceived useful and easy-to-use. The main contributions of this study are the elements of usable e-government portals for Iraqi context and the prototype of the usable portal called IegP.